Biofuel mandate versus favourable taxation of electric cars. The case of Norway - Geir H. Bjertnæs (Statistics Norway, Research Department, 2013)
This study investigates whether biofuel policies or favourable taxation of electric cars should be employed to satisfy a green house gas emission target connected to private transport within the Norwegian economy. The study shows that implementation of biofuel generates a welfare gain in the presence of the current favourable taxation of electric cars in Norway. Implementation of biofuels, however, generates a welfare loss when the tax rate on purchase of electric cars is increased to the average tax rate on purchase of diesel powered cars.
Keywords: Q54; R48; H23; 330; Biofuel; Mandates; Electric cars; Greeen house gas emissions